Belajar Praktis Bahasa Inggris, A Source for Developing Eleventh Graders’ Speaking Skill (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
The objectives of the research are to describe Belajar Praktis Bahasa Inggris, a source for developing eleventh graders’ speaking skill and to know whether or not the speaking activities belong to communicative activity based on the theory of William Littlewood about communicative activity. This research is descriptive qualitative research in the type of documentary or content analysis. The data source that is used is textbook entitled “Belajar Praktis Bahasa Inggris” for eleventh graders. The data will be analyzed by using Richard’s theory (2015) about genres of spoken interaction and Littlewood’s theory (2014) about communicative activity. There are some steps in analyzing data. The first step is familiarizing and organizing, the second is coding and reducing, the last is interpreting and representing. The research based on Richard’s theory (2015), there are out of five kinds of speaking activity that are found in the textbook. Those are small talk, conversation, discussion, and presentation. There are four categories of communicative activity that are found in the textbook. Those are pre-communicative language practice that is about 20%, communicative language practice in about 33.3%, structured communication 6.7%, and authentic communication 40%. In conclusion, this textbook belongs to communicative activity because there is no activity that is categorized as non-communicative learning.
Keywords: belajar praktis bahasa inggris, developing, speaking skill